Ecoliteracy in English for Tourism: Exploring lecturers’ perspectives and challenges in an Indonesian vocational higher education setting - Indrastana, Nodistya Septian; Novawan, Adriadi; Wicaksono, Julien Arief; Rinda, Renata Kenanga (International Journal of Studies in Social Sciences and Humanities, 2026)
Environmental sustainability is becoming increasingly significant in tourism education. However, incorporating ecoliteracy into English for Specific Purposes (ESP) courses remains limited within vocational settings. This qualitative case study explored how English for Tourism lecturers at an Indonesian vocational college perceive ecoliteracy integration and the challenges they encounter. Three lecturers participated in semi-structured interviews, which were supplemented with analysis of course materials. The results showed four positive perspectives: ecoliteracy enhances practical learning, encourages a comprehensive understanding of the interconnectedness between society, economy, and environment, aligns with industry sustainability expectations, and develops 21st-century skills. Nonetheless, three major challenges were identified: difficulty aligning the curriculum, limited time for developing materials, and insufficient content knowledge in sustainability education. The study highlights that although lecturers see the value of ecoliteracy, institutional support, such as curriculum reform, resource availability, and ongoing professional development, is crucial for effective integration. These insights contribute to understanding teacher cognition in ESP and have implications for policy and professional growth in vocational training.